Legal Analysis of The Legal Regulations for The Return of Confiscated Items Based on Article 133 of the Kuhap - Urip Tri Gunawan; Muhammad Taufiq (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2026)
This study aims to analyze the legal provisions regarding the return of confiscated objects after a pretrial decision based on Article 133 of Law Number 20 of 2025 concerning the Criminal Procedure Code (KUHAP), and to examine the legal status and force of pretrial decisions in the criminal justice system in Indonesia. The type of research used in this study is Normative Juridical legal research. The results of the study indicate that Article 133 of Law Number 20 of 2025 concerning the Criminal Procedure Code has basically provided a clear normative basis regarding the obligation to return confiscated objects to the entitled party if the objects are no longer needed in the evidentiary process. This provision reflects the principle of property rights protection and the principle of legal certainty in the criminal justice system. In addition, a pretrial decision declaring a confiscation invalid has binding legal force and must be implemented as a form of restoration of the original state (restitutio in integrum). However, the Criminal Procedure Code has not yet expressly regulated the mechanism for executing pretrial decisions, thus creating obstacles in their implementation.